Lean Six Sigma Tools to Improve Business Result at PHN Industry Sdn. Bhd. - Sabaruddin, Abu (2016)
This project paper is a case study conducted at PHN Industry Sdn. Bhd, a company jointly owned by DRB-HICOM Berhad and PROTON Holdings Sdn. Bhd. It produces automotive compenents for major Original Equipment Manufacturers (OEMs), namely, PROTON, PERODUA and HONDA. The company specializes in the metal stamping, compenents assembly, roll forming and dies manufacturing. However, cost efficiency is a recurring issue; the management has consistently been searching for solutions to reduce increasing cost of metal compenents and to eliminate waters in production processes. Also, business profits have been challenged by increasing competition in an increasing saturated automotive market